Empirical Measure of Multivariate Complete Dependence: Anusart Kinon - Team, Support (Thai Journal of Mathematics, 2022)
In this work, we constructed a kernel-based estimator for measure of complete dependence in the case of random response vectors. Asymptotic properties of this estimator were proved. Simulation studies have also been done to confirm the result.